Eksistensi Pasraman Dalam Menanamkan Nilai Moral Bagi Umat Hindu - I Putu Suarnaya (Jayapangus Press, 2020)
Bali Island as a foreign tourist destination, aware or not possible to be affected by the interaction with tourists who come to Bali and cause acculturation of foreign culture with local culture. Acculturation of positive culture enriches local culture while the influence of negative foreign culture can damage, mencedrai and even shift the existence of local culture, for that the necessary antidote to negative foreign culture through education in pasraman. The aim of this study. describe the existence of pasraman Brahma Vidya Samgraha Penarungan Village, Buleleng Regency; Describe the implementation of education in Pasraman Brahma Vidya Samgraha; Penarungan Village, Buleleng Regency; Describing the planting of moral education in the Brahma Vidya Samgraha Penarungan Village, Buleleng Regency. This research uses descriptive-qualitative method with a phenomenological approach. The findings in this study of the existence of Pasraman Brahma Vidya Samgraha are an acculturation of the education system that is the traditional education system and the modern or contemporary education system. The implementation of ceremonies (rituals) through the routine of making ceremonial facilities carried out in pasraman. Conclusion: Pasraman Brahma Vidya Samgraha is a type of non-formal education acculturated with the education system of Color Dormitory Dharma with the transformation of the upanisad learning model based on vedic culture; Pasraman Brahma Vidya Samgraha conducts adult learning (andragogy) with teaching programs in accordance with the level of basic education, middle level education and primary level of education, by applying a varied upanisad learning model; Pasraman Brahma Vidya Samgraha implements moral values ​​in Pasraman as a spiritual commitment through the mutual assistance activities of the sisya in the process of making ceremonies and conducting ceremonies in Pasraman.